Improved Gradient-Based Optimizer for Modelling Thermal and Hydropower Plants - Ahmed M. Agwa; Yehya I. Mesalam; Mohamed H. Hassan; Mahmoud A. El-Dabah; Anas M. El-Sherif; Salah Kamel (International Transactions on Electrical Energy Systems)
Adequate and accurate models of thermal power plants (TPP) and hydropower plants (HPP) are of great importance for the optimal economic functioning of electric power systems. The extracted models have a direct impact on economic dispatch calculations. In this research, a modified optimization algorithm called an improved gradient-based optimizer (IGBO) is deployed for the optimal extraction of TPP and HPP input-output parameters. Firstly, the IGBO is tested for use with well-known benchmark functions and shows outstanding performance over the original GBO and other competitive algorithms. For the input-output parameters extraction of TPP and HPP, the sum of the absolute error (SAE) is utilized as a fitness function to be minimized. Secondly, nine models of TPP and HPP are employed for parameter identification using IGBO. Simulation outcomes prove the capability of IGBO to accurately extract input-output parameters of TPP and HPP. Moreover, the convergence characteristics of IGBO are remarkable among investigated optimization algorithms.